Can HbA1C be used to predict which patients are at risk for developing type 2 diabetes mellitus?. Issue 2 (February 2017) - Trieu, Young; Zawi, Rami; Khunti, Amar; Miller, Barbara
Abstract : EVIDENCE‐BASED ANSWER : Glycosylated hemoglobin (HbA1C) 5.3%‐6.4% has a similar predictive value to fasting plasma glucose (FPG) >99 mg/dL over 5 to 6 years; an abnormal result on both measures is more predictive of developing type 2 diabetes mellitus (DM2) than an abnormal result on either test alone (SOR: C, consistent cohort studies of disease oriented outcomes).